Percutaneous treatment of anomalous systemic artery to pulmonary venous fistulas in children: Description of three cases and review of the literature - Giuseppe Antonio Mazza; MariangelaGarofalo; GabriellaAgnoletti (Wolters Kluwer Medknow Publications, 2021)
In the normal lung, the only communications between the systemic and pulmonary arterial systems are the connections between the bronchial and pulmonary arteries that occur at the respiratory bronchioles, where pulmonary and bronchial capillaries freely anastomose. Rarely, anomalous connections can occur between normal or aberrant systemic arteries and pulmonary vessels. We performed a comprehensive literature review of all available manuscripts on PubMed and Google Scholar that included a case report or case series with diagnosis of systemic artery to pulmonary venous fistulas who underwent percutaneous treatment. Furthermore, we report three cases of children diagnosed and treated in our Pediatric Cardiology Center.